Effect of Mound Soil on Concrete Produced with River Sand - Mbadike, Elivs M.; Osadebe, N.N (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
In this research work, the effect of mound soil on concrete produced with river sand was investigated. A mixed proportion of 1.1.8:3.7 with water cement ratio of 0.47 were used. The percentage replacement of river sand with mound soil is 0%, 5%, 10%, 20%, 30% and 40%. Concrete cubes of 150mm x 150mm x150mm of river sand/mound soil were cast and cured at 3, 7, 28, 60 and 90 days respectively. At the end of each hydration period, the three cubes for each hydration period were crushed and their average compressive strength recorded. A total of ninety (90) concrete cubes were cast. The result of the compressive strength test for 5- 40% replacement of river sand with mound soil ranges from 24.00 -42.58N/mm2 a against 23.29-36.08N/mm2 for the control test (0% replacement).The workability of concrete produced withÂ 5- 40% replacement of river sand with mound soil ranges from 47- 62mm as against 70mm for the control test.